How to do better research - Menezes, M. N. (Demerara Pub. GeorgetownGY, 1990)
Provides methods and techniques for writing research papers especially in the discipline of History. Seeks to impart the skills needed for READING and WRITING history. Distinguishes between external and internal criticism, and explains how to review a book. Lists 13 qualities of a good historical essay, and addresses skill areas including: gathering, interpreting and analysing written and oral source material; writing bibliographies and footnotes; and, planning and writing the thesis.